State of the scientific knowledge on properties and genesis of Anthropogenic Dark Earths in Central Amazonia (terra preta de Índio) - Glaser, Bruno; Birk, Jago Jonathan (Geochimica et cosmochimica acta, 2012)
Tropical rainforests are highly important for the global climate regulation and for global biodiversity. However, these ecosystems are characterized by nutrient-poor and highly weathered soils and by high turnover rates of organic matter. Thus, they are fragile ecosystems prone to loss of ecosystem services when anthropogenically disturbed. Currently, the major threat to these ecosystems is deforestation leading to irreversible destruction of rainforests. Surprising and not expected is that within these ecosystems small patches of highly fertile soils occur which are known as Anthropogenic Dark Earths or terra preta de Índio (terra preta). These soils exhibit high nutrient and soil organic matter stocks and allow sustainable agriculture. Frequent occurrence of pot-sherds of pre-Columbian origin and further evidence for settlement activities clearly demonstrate that terra preta is of anthropogenic origin. In recent years, the terra preta phenomenon has gained increasing interest because it is assumed that terra preta could act as a model for promoting sustainable agricultural practices in the humid tropics and because terra preta is an example for long-term CO2 sequestration into terrestrial ecosystems with additional positive benefits for ecosystem services. These potentials of terra preta initiated a great number of studies but also stimulated fantasy about their genesis. Therefore, the aim of this review is to summarize the scientific knowledge about terra preta properties and to discuss their genesis. From our own and literature data it is evident that terra preta is the product of inorganic [e.g. ash, bones (esp. fish)] and organic (e.g. biomass wastes, manure, excrements, urine, and biochar) amendments to infertile Ferralsols. These ingredients were microbially metabolized and stabilized by humification in soil, fungi playing a bigger role in this process compared to bacteria in surrounding ecosystems. Biochar is a key component for this process due to its stability and its enrichment in terra preta. It is still unclear if terra preta was produced intentionally or un-intentionally. In addition, it is unclear how much time was needed after the disposal of the materials mentioned above to develop a terra preta. Further research is highly desired to investigate these latter two issues.